The steps used to solve the quadratic equation are
8(x2 + 2x) = –3
8(x2 + 2x + 1) = –3 + 8
x = –1 Plus or minus StartRoot StartFraction 5 Over 8 EndFraction EndRoot
Given the equation;
8x² + 16x + 3 = 0
Collect like terms
8x² + 16x = -3
Take the common factors, we have
8(x² + 2x) = -3
Completing squares in the brackets and balancing the equation in the right side
8(x² + 2x + 1) = -3 + 8
Factoring the perfect square
[tex]8(x + 1)^2} = 5[/tex]
Make 'x' subject
[tex](x + 1)^2= \frac{5}{8}[/tex]
[tex](x + 1) =[/tex] ±[tex]\sqrt{\frac{5}{8} }[/tex]
[tex]x =[/tex] -1 ±[tex]\sqrt{\frac{5}{8} } }[/tex]
Thus, we can clearly see the steps used to solve the quadratic equation are
8(x2 + 2x) = –3
8(x2 + 2x + 1) = –3 + 8
x = –1 Plus or minus StartRoot StartFraction 5 Over 8 EndFraction EndRoot
Learn more about quadratic equations here:
https://brainly.com/question/1214333
#SPJ1